A new species of Iconella (Mason, 1981) (Hymenoptera, Braconidae, Microgastrinae), a parasitoid of Melitara subumbrella (Dyar, 1925) cactus moth larvae from New Mexico with biological notes and an updated key to the American Iconella species - Colin R. Morrison; Wyatt R. Armstrong; Robert M. Plowes; Lawrence E. Gilbert; José L. Fernández-Triana (Journal of Hymenoptera Research)
We describe the wasp Iconella melitaraevora sp. nov. (Braconidae, Microgastrinae), a parasitoid of Melitara subumbrella caterpillars (Lepidoptera, Pyralidae, Phycitinae). Multiple wasp cohorts were reared from hosts collected in a montane dryland habitat of New Mexico, USA. This is the first case of gregariousness in Iconella. An updated key to American Iconella species is provided. We present a maximum likelihood tree using the cytochrome c oxidase subunit I (COI) locus of this species relative to other described Iconella species from the Americas. We also describe the biology and environmental conditions where Iconella melitaraevora sp. nov. was discovered in the context of its prickly pear cactus (Opuntia Mill.) herbivore host. The potential biological control capacity of microgastrine wasps which attack prickly pear specialist herbivores is discussed.